Varietal and trait preferences for boiled sweetpotato in urban Hanoi and implications for breeding - Vu, T.M.H.; Tu, V.P.; Naziri, D. (Wiley, 2024)
Cognizant of the need to refocus breeding efforts toward end-product quality traits taking into account the preferences of consumers and in consideration of the rapid urbanization in South-eastern Asia, this study investigated the consumer's preferences for sweetpotato in Hanoi. Using a mixed-methods research design, the study identified the most preferred and least preferred attributes of both the fresh and boiled product, disaggregated by gender, age, and socioeconomic status. Preferences and associated traits of six popular varieties were determined. Results indicate that while these varieties largely already meet consumers' preferences, consumers have a clear preference for a few varieties for which marginal adjustments are needed to further increase their acceptability among the growing urban population. Our findings indicate the direction of these adjustments and can contribute to inform demand-led national and international breeding programs and, ultimately, to higher and faster variety uptake and adoption.